Stress reactivity and maternal health (STRIVE): protocol for a multisite observational cohort study - Kiarri N Kershaw; Brittney Williams; William A Grobman; Lynn M Yee; Anna Bartholomew; Shaina J Alexandria; Lauren Hoffer; Grace D Achepohl; Stephanie Brindle; Heather Frey (BMJ Open)
Introduction Black adults are generally exposed to more stressors over the life course and, due to the intersections of racism and economic and social resources, they tend to have more limited resources to cope with social stressors than white adults. This mismatch between stress exposures and resources may lead to dysregulated responses or reactivity to stressors and contribute to persistent racial disparities seen in adverse pregnancy outcomes (APOs). Prior studies examining stress exposures have been hampered by the challenge of capturing stress exposures comprehensively, given they are manifold, dynamic and accumulate over time. The Stress Reactivity and Maternal Health Study seeks to overcome this limitation by examining the impact of physiological and psychological stress reactivity to everyday stressors on APOs.Methods and analysis We are recruiting 700 nulliparous self-identified non-Hispanic black and white pregnant individuals from academic medical centres in the USA. We use ecological momentary assessments administered via smartphones to collect repeated measurements of exposure to everyday stressors throughout the day over the course of seven consecutive days at two different time points mid-pregnancy (14–22 weeks and 22–28 weeks). At the same time, we collect intensive measurements of heart rate variability, blood pressure, salivary cortisol and positive and negative affect. We will use mixed-effects models to estimate personalised indicators of cardiovascular, neuroendocrine and affective reactivity to everyday stressors. We will then use linear and logistic regression modelling to examine associations of these personalised indicators of stress reactivity with placental histological lesions and the occurrence of APOs. Finally, we will use the gap-closing estimand method to quantify the extent to which racial disparities in adverse placental and pregnancy outcomes are explained by differences in prenatal stress exposure and prenatal stress reactivity.Ethics and dissemination The Northwestern University institutional review board (IRB) approved this study and serves as the single IRB of record (STU00218683). All participants will sign an informed consent document prior to participation, and data will be treated confidentially. Findings will be disseminated in peer-reviewed scientific journals, briefs, infographics and presentations.